Light and Temperature Shape the Phenylpropanoid Profile of Azolla filiculoides Fronds - Costarelli, Alma; Cannavò, Sara; Cerri, Martina; Pellegrino, Roberto Maria; Reale, Lara; Paolocci, Francesco; Pasqualini, Stefania (Frontiers in Plant Science, 2021)
Azolla is a genus of floating freshwater ferns. By their high growth and N2 fixation rates, Azolla species have been exploited for centuries by populations of South-east Asia as biofertilizers in rice paddies. The use of Azolla species as a sustainable plant material for diverse applications, such as feeding, biofuel production, and bioremediation, has encountered a growing interest over the last few years. However, high levels of feed deterrent flavonoids in their fronds have discouraged the use of these ferns as a sustainable protein source for animal consumption. Additionally, information on how and to what extent environmental determinants affect the accumulation of secondary metabolites in these organisms remains poorly understood. Moving from these considerations, here, we investigated by an untargeted metabolomics approach the profiles of phenylpropanoid compounds in the fronds of Azolla filiculoides sampled under control and pigment-inducing stress conditions. In parallel, we assayed the expression of essential structural genes of the phenylpropanoid pathway by quantitative RT-PCR. This study provides novel information concerning A. filiculoides phenylpropanoid compounds and their temporal profiling in response to environmental stimuli. In particular, we show that besides the already known 3-deoxyanthocyanidins, anthocyanidins, and proanthocyanidins, this fern can accumulate additional secondary metabolites of outstanding importance, such as chemoattractants, defense compounds, and reactive oxygen species (ROS) scavengers, and crucial as dietary components for humans, such as dihydrochalcones, stilbenes, isoflavones, and phlobaphenes. The findings of this study open an opportunity for future research studies to unveil the interplay between genetic and environmental determinants underlying the elicitation of the secondary metabolites in ferns and exploit these organisms as sustainable sources of beneficial metabolites for human health.